2019
DOI: 10.1029/2018ef000811
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Carbon Emission Linkages Across Boundaries

Abstract: Cities are increasingly linked to domestic and foreign markets during rapid globalization of trade. While transboundary carbon footprints of cities have been recently highlighted, we still have limited understanding of how carbon emission linkages between sectors are reshaping urban carbon footprints through time. In this study, we propose an integrated input‐output approach to trace the dynamics of various types of carbon emission linkages associated with a city. This approach quantifies full linkages in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…Fossil fuel combustion-related virtual carbon, as part of cities' carbon metabolism via upstream activities, is also found to play a large part in TCI. Most cities in our study, outsource a considerable proportion of their carbon emissions by producing electricity upstream and importing materials, goods and services, significantly amplifying the climatic impact of the urban economy, similar to observations in prior studies 14,19,20 . Peters et al 36 reported virtual gaseous carbon contributed half of total carbon related to international trade.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Fossil fuel combustion-related virtual carbon, as part of cities' carbon metabolism via upstream activities, is also found to play a large part in TCI. Most cities in our study, outsource a considerable proportion of their carbon emissions by producing electricity upstream and importing materials, goods and services, significantly amplifying the climatic impact of the urban economy, similar to observations in prior studies 14,19,20 . Peters et al 36 reported virtual gaseous carbon contributed half of total carbon related to international trade.…”
Section: Resultssupporting
confidence: 87%
“…3). Studies have reported that upstream emissons have a considerable influence on the urban carbon balance 14,15,20 . Our work further articulates that upstream emissions are significant even when they are accounted for in a broader context of the carbon metabolism that includes both physical and virtual carbon streams.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is thus considered a sound and relevant methodology for consumption-based accounting when studying trade-related impacts at global or national levels. Linked with inventories of emissions (e.g., air pollutants and CO 2 ), resources (e.g., water and land), and other environmental indicators, the environmental-extended multiregional input-output analysis can quantify different types of environmental impacts through complex cross-regional supply chains, including air pollutants (Lin et al, 2014), CO 2 emissions (Chen et al, 2019;Feng et al, 2013;Pan et al, 2017), energy use (Mi, Zheng, et al, 2018), resource consumption (Wiedmann, 2009), and environmental damage (Wang, Liu, et al, 2017). We also use the MRIO model to quantify the value added along supply chains, following previous studies (Ou et al, 2019;Wu et al, 2018;Zhang, Li, et al, 2018).…”
Section: Environmental-extended Mrio Frameworkmentioning
confidence: 99%